GATA6‐positive lung adenocarcinomas are associated with invasive mucinous adenocarcinoma morphology, hepatocyte nuclear factor 4α expression, and KRAS mutations. Issue 1 (17th April 2018) - Nakajima, Naoki; Yoshizawa, Akihiko; Nakajima, Tomoyuki; Hirata, Masahiro; Furuhata, Ayako; Sumiyoshi, Shinji; Rokutan‐Kurata, Mariyo; Sonobe, Makoto; Menju, Toshi; Miyamoto, Ei; Chen‐Yoshikawa, Toyofumi F; Date, Hiroshi; et al.
Abstract : Aims: GATA6 is known to play a role in lung development. However, its role in the carcinogenesis of lung cancer is not well studied. The aim of this study was to analyse GATA6 expression in lung adenocarcinomas (LAs) by immunohistochemistry (IHC) in order to define its association with clinicopathological characteristics. Methods and results: IHC analysis of GATA6 was performed with tissue microarray slides containing 348 LAs. The association between GATA6 expression and clinicopathological parameters was evaluated. GATA6 expression in epithelial tumours other than lung cancer was also evaluated. GATA6 expression was found in 47 LAs (13.5%). This occurred more frequently in younger patients ( P = 0.005), and was associated with the absence of lymph node metastasis ( P =0.024), well‐differentiated to moderately differentiated tumours ( P < 0.001), the absence of lymphatic invasion ( P = 0.020), and the absence of vascular invasion ( P = 0.011). GATA6 expression was associated with mucin production ( P < 0.001), the invasive mucinous adenocarcinoma subtype ( P < 0.001), KRAS mutations ( P = 0.026), expression of MUC2 ( P < 0.001), CDX2 ( P = 0.049), and MUC5AC ( P < 0.001), and absence of expression of TTF‐1 ( P = 0.002). GATA6 expression was also associated with hepatocyte nuclear factor 4α (HNF4α) expression ( P < 0.001). GATA6 expression tended to indicate better prognoses, whereas patients with HNF4α expression had significantly worse prognoses ( P = 0.033). Of 270 tumours other than lung cancer, 110 expressed GATA6. Conclusions: These findings suggest that GATA6 might interact with HNF4α and contribute to the development of mucinous‐type LAs.